THE PRINCIPLE OF FORMING LEXICOGRAPHIC COMPETENCE IN PRIMARY CLASS STUDENTS AND TECHNOLOGIES - Buvajonova Mahirakhan Usmanali kizi; Abdulhamidova Naimakhan Mirzahid kizi (Zeta Repository, 2023)
In this article, you can get enough information about the principles and technologies of the modern approach to the formation of lexicographic competence in elementary school students.